Mindfulness Dengan Kesejahteraan Psikologis (Psychological Well-Being) Pada Mahasiswa - pratama, yoga; putri puspitasari, rahmah (Universitas Darul Ulum, 2023)
his research aims to determine the relationship between mindfulness and psychological well-being in students. This research involved 50 students from the psychology faculty at Darul Ulum University, Jombang. The data collection technique was carried out online using Google Form using purposive random sampling technique. Based on the results of the Pearson correlation test analysis, the correlation coefficient (rxy) = 0.911 with a significance value of 0.000 (ρ<0.05) was obtained. This shows that there is a significant positive correlation between mindfulness and psychological well-being in students.